Analysis and Optimization of SPM-based 2R Signal Regeneration at 40 Gb/s - Striegler, Arne; Schmauß, Bernhard (Journal of Lightwave Technology, 2006)
In order to maintain a signal quality and to enhance the robustness of long haul transmission, optical regenerators have been developed and investigated during the last few years. This paper provides a detailed analysis of self-phase modulation (SPM)-based 2R signal regeneration by an analysis of the spectrum of a single pulse. A model is presented to explain the principle of ghost-pulse suppression and amplitude-jitter reduction and to derive design rules to optimize signal regeneration at 40 Gb/s. Finally, the influence of the fiber dispersion on the regeneration is discussed. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.LEH.analys
Keywords: All-optical regeneration; Nonlinear-fiber (NLF) effects; Self-phase modulation (SPM)